Diagnosis and categorization of malignant effusions: A 6‐year review from a single academic institution. Issue 5 (10th April 2020) - Lew, Madelyn; Cantley, Richard; Heider, Amer; Jing, Xin
Abstract: Background: Cytologic detection of malignant cells in pleural, peritoneal, or pericardial effusion most likely indicates advanced stage of malignant disease. There are a few studies updating the categorization of malignant effusions. Methods: The electronic pathology database was searched to identify consecutive cases of malignant effusion during a 6‐year period. Patient age and gender, origins of known malignancy, and cytologic diagnoses were recorded and summarized. Results: A total of 1059 specimens included 561 (53%) pleural, 441 (41.6%) peritoneal, and 57 (5.4%) pericardial fluids. Most of the pleural (516, 92.0%), peritoneal (418, 94.8%), and pericardial (53, 93.0%) specimens were derived from patients with a single known malignancy. More common origins involving pleural fluid were lung (152, 27.1%) followed by breast (103, 18.4%) and gastrointestinal tract (76, 13.5%). The most common etiology for women and men was breast (102, 30.8%) and lung (67, 36.2%), respectively. More common origins involving peritoneal fluid were gastrointestinal (158, 35.8%) and gynecologic (156, 35.4%) tracts, and breast (46, 10.4%). The most common etiology for women and men was Mullerian (156, 55.5%) and gastrointestinal tract (94, 68.6%), respectively. Most common origins involving the pericardial fluid were breast (20, 37.7%) and lung (17, 29.8%). Breast and lung were the most common etiology for women (20, 57.1%) and men (8, 44.4%), respectively. Conclusions: Breast and lung remain to be the most common origin of both malignant pleural and pericardial effusion for women and men, respectively. The most common origin involving peritoneal effusion is Mullerian for women and gastrointestinal tract for men.